2011
DOI: 10.1007/s12311-011-0297-7
|View full text |Cite
|
Sign up to set email alerts
|

Increased Number of Cerebellar Granule Cells and Astrocytes in the Internal Granule Layer in Sheep Following Prenatal Intra-amniotic Injection of Lipopolysaccharide

Abstract: Chorioamnionitis is an important problem in perinatology today, leading to brain injury and neurological handicaps. However, there are almost no data available regarding chorioamnionitis and a specific damage of the cerebellum. Therefore, this study aimed at determining if chorioamnionitis causes cerebellar morphological alterations. Chorioamnionitis was induced in sheep by the intra-amniotic injection of lipopolysaccharide (LPS) at a gestational age (GA) of 110 days. At a GA of 140 days, we assessed the mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 84 publications
2
9
0
Order By: Relevance
“…The significant increase in the density of granule cells in the IGL of LPS-exposed animals was unexpected but is in accordance with the findings of Strackx et al ( 2012 ) who reported an increase in total granule cell number in the IGL 30 days after LPS exposure. Although we were not able to calculate total neuronal numbers, the finding that the cross-sectional area of the IGL was not different from controls suggests that the increase in density might have resulted in an increase in total granule cell numbers.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The significant increase in the density of granule cells in the IGL of LPS-exposed animals was unexpected but is in accordance with the findings of Strackx et al ( 2012 ) who reported an increase in total granule cell number in the IGL 30 days after LPS exposure. Although we were not able to calculate total neuronal numbers, the finding that the cross-sectional area of the IGL was not different from controls suggests that the increase in density might have resulted in an increase in total granule cell numbers.…”
Section: Discussionsupporting
confidence: 92%
“…In accordance with the only study to examine the effects of chorioamnionitis in the human infant cerebellum (Limperopoulos et al, 2005 ), we did not find any gross injury such as focal infarcts or hemeorrhage in the LPS-exposed cerebellar cortex or WM in this, or our previous study (Duncan et al, 2002 ). Strackx et al ( 2012 ) also reported no overt cerebellar damage in a similar sheep model of inflammation although Dean et al ( 2009 ) found some focal lesions in animals exposed to LPS at an earlier gestational age (93-96 DGA). Studies that have characterized LPS-induced WM injury at the cellular level report finding microgliosis, astrogliosis, increased apoptosis, decreased maturation of oligodendrocytes, and compromised blood-brain barrier integrity (Hutton et al, 2007 ; Dean et al, 2009 ; Gavilanes et al, 2009 ; Strackx et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To test this hypothesis, we used a sheep model in which lipopolysaccharide (LPS) was injected intravenously in instrumented fetal lambs. Our group has developed several well established sheep models to study both the effects of chorioamnionitis and endotoxemia/sepsis on the fetal brain (20)(21)(22)(23). In this study, the (cyto-) architecture of the cingulate cortex (CC) was examined using immunohistochemistry with focus on the different subsets of GABA-ergic interneurons which were shown to play a major role in the pathogenesis of schizophrenia.…”
Section: Introductionmentioning
confidence: 99%